2018
DOI: 10.17826/cumj.341649
|View full text |Cite
|
Sign up to set email alerts
|

Serum neutrophil-lymphocyte ratios, C-reactive protein and sedimentation levels in Parkinson's disease

Abstract: ÖzPurpose: We aimed to investigate the systemic inflammation status by analyzing the Neutrophil/Lymphocyte (N/L) ratio, Erythrocyte Sedimentation Rate (ESR), and C -reactive protein (CRP) in patients with Parkinson's disease (PD). Materials and Methods: 101 PD patients, and 60 healthy subjects of similar age and gender were include in this study. The demographic data and duration of the disease, the drugs, duration of usage of Parkinson drugs, Hoehn-Yahr stage were noted. After full neurological examination bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…Akıl and colleagues [ 24 ] found that NLR values ≥ 2.25 resulted in 73% sensitivity and 74% specificity in identifying PD patients, determining higher predictive power than carcinoembryonic antigen (CEA). Similarly, another study [ 25 ] established a cut-off value of 2.39 with 65% sensitivity and 75% specificity (AUC = 0.714). Compared to these results, the present research showed for NLR lower AUC values and poorer prediction of PD diagnosis: however, it should be borne in mind that in our case-control design strict matching criteria, including cardiovascular comorbidities, were applied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Akıl and colleagues [ 24 ] found that NLR values ≥ 2.25 resulted in 73% sensitivity and 74% specificity in identifying PD patients, determining higher predictive power than carcinoembryonic antigen (CEA). Similarly, another study [ 25 ] established a cut-off value of 2.39 with 65% sensitivity and 75% specificity (AUC = 0.714). Compared to these results, the present research showed for NLR lower AUC values and poorer prediction of PD diagnosis: however, it should be borne in mind that in our case-control design strict matching criteria, including cardiovascular comorbidities, were applied.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the relationship between NLR and PD-related symptoms, another work [ 26 ] failed to find statistically significant differences in NLR between 13 akinetic-rigid and 33 tremor-dominant patients. Furthermore, no association with disease severity [ 10 , 27 ] and controversial results concerning the relationship with disease duration and LEDD [ 10 , 25 , 26 ] have also been described.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between the NLR and PD incidence remains controversial. A previous study reported a positive correlation between the NLR and disease duration and between the Hoehn and Yahr staging scale (H&Y) score and PD incidence ( 24 ), while another study reported conflicting results ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…We observed the high-risk score patients with increased monocytes compared to the low-risk score patients (nominal p < 0.05, but no statistical significance after multiple testing correction) were correlated with the severity progression of motor symptoms in PD. Several studies have demonstrated that neutrophils or the neutrophil-to-lymphocyte ratio (NLR) were increased in patients with PD compared to healthy controls [50][51][52], and Solmaz et al [53] found a positive correlation between the NLR and H&Y stage. Our study showed a significant increase in neutrophils with a concomitant decrease in B cells and CD4 + T cells in PD cases with high-risk scores, which is in line with previous reports [53,54].…”
mentioning
confidence: 99%
“…Several studies have demonstrated that neutrophils or the neutrophil-to-lymphocyte ratio (NLR) were increased in patients with PD compared to healthy controls [50][51][52], and Solmaz et al [53] found a positive correlation between the NLR and H&Y stage. Our study showed a significant increase in neutrophils with a concomitant decrease in B cells and CD4 + T cells in PD cases with high-risk scores, which is in line with previous reports [53,54]. Accumulated evidence showed that CD4 + T cells can infiltrate the brain to induce dopaminergic toxicity and contribute to neurodegeneration in PD [55,56].…”
mentioning
confidence: 99%